2011
DOI: 10.1007/s10578-011-0217-6
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Resolution of Their Young Children’s Psychiatric Diagnoses: Associations with Child, Parent, and Relationship Characteristics

Abstract: Maternal resolution of a child's diagnosis relates to sensitive caregiving and healthy attachment. Failure to resolve is associated with maternal distress, high caregiving burden, and the quality of marital and social support. This study examined maternal resolution of diagnosis in a child psychiatric population utilizing the Reaction to Diagnosis paradigm. Thirty-three mothers of children ages 2–7 years with psychiatric disorders were interviewed using the Reaction to Diagnosis Interview. Slightly over half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…Furthermore, resolved mothers had significantly more securely attached children and reported significantly lower levels of stress compared to unresolved mothers. These results were further replicated in numerous studies which included parents of children with CP (Marvin & Pianta, ; Pianta et al., ; Rentinck et al., ; Schuengel et al., ; Sheeran, Marvin, & Pianta, ), Phenylketonuria (PKU; Lord, Ungerer, & Wastell, ), Autism Spectrum Disorders (ASD; Milshtein, Yirmiya, Oppenheim, Koren‐Karie, & Levi, ; Oppenheim, Koren‐Karie, Dolev, & Yirmiya, ; Wachtel & Carter, ), Intellectual disability (Feniger‐Schaal & Oppenheim, ), and other psychiatric and neurological conditions (Barnett et al., ; Kearney, Britner, Farrell, & Robinson, ). In these studies, the rates of resolution among parents ranged from 30% to 82% and parental resolution was repeatedly associated with child's secure attachment.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, resolved mothers had significantly more securely attached children and reported significantly lower levels of stress compared to unresolved mothers. These results were further replicated in numerous studies which included parents of children with CP (Marvin & Pianta, ; Pianta et al., ; Rentinck et al., ; Schuengel et al., ; Sheeran, Marvin, & Pianta, ), Phenylketonuria (PKU; Lord, Ungerer, & Wastell, ), Autism Spectrum Disorders (ASD; Milshtein, Yirmiya, Oppenheim, Koren‐Karie, & Levi, ; Oppenheim, Koren‐Karie, Dolev, & Yirmiya, ; Wachtel & Carter, ), Intellectual disability (Feniger‐Schaal & Oppenheim, ), and other psychiatric and neurological conditions (Barnett et al., ; Kearney, Britner, Farrell, & Robinson, ). In these studies, the rates of resolution among parents ranged from 30% to 82% and parental resolution was repeatedly associated with child's secure attachment.…”
Section: Introductionmentioning
confidence: 74%
“…() who found that parents reports of their mental health status was not associated with resolution. However, parenting stress and depression were previously reported as associated with parental resolution for samples of children with CP, Epilepsy, PKU, and psychiatric disorders (Kearney et al., ; Lord et al., ; Marvin & Pianta, ). These inconsistent findings merit further investigation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The acceptance, or denial, of diagnosis significantly influences parenting styles. For example, mothers who are unresolved regarding their child's diagnosis show less sensitivity to their child's signals [69,70], and greater resolve has been correlated not only to positive parenting behavior but also to less parental stress [e.g., 70]. These resolutions support the need for parent interventions targeted toward addressing the common stages of adjustment experienced by parents of children with disabilities such as various forms of shock, denial, acceptance [e.g., 71], and to move parents quickly to acceptance and to more active, positive coping [e.g., 72,73].…”
Section: Impact Of Parent Characteristics and Parentingmentioning
confidence: 99%
“…Ono što je važno naglasiti jeste da roditelji koji prihvate detetovo stanje realno sagledavaju njegove mogućnosti i sopstvenu starateljsku ulogu [4]. Nasuprot njima, roditelji koji ne prihvataju dijagnozu doživljavaju distres kada brinu o svom detetu što smanjuje njihovu emotivnu prijemčivost i otežava prepoznavanje detetovih potreba [12,13]. Prikaz druge majke ukazuje na njenu preokupiranost ljutnjom, naroči-to usmerenu prema zdravstvenom osoblju, čak i onima koji aktuelno pomažu njenom detetu.…”
Section: Diskusijaunclassified